Normability and Duality in the Two-Dimensional Lorentz Spaces - Jain, Pankaj; Jain, Sandhya (Eurasian Mathematical Journal, 2014)
The two-dimensional Lorentz space \( L_2^{p,q} \) is defined as a special case from the two-dimensional space \( Λ_2^p(w) \) just as was done in the classical dimension one. The normability and duality of the space \( L_2^{p,q} \) are discussed.